2008
DOI: 10.1038/ijo.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

Methyl donor supplementation prevents transgenerational amplification of obesity

Abstract: Background: The obesity epidemic, recognized in developed nations for decades, is now a worldwide phenomenon. All age groups are affected, including women of childbearing age, fueling concern that maternal obesity before and during pregnancy and lactation impairs developmental establishment of body weight regulatory mechanisms in the fetus or infant, causing transgenerational amplification of obesity prevalence and severity. The biological mechanisms underlying such processes remain unknown. Methods: We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
262
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(270 citation statements)
references
References 25 publications
4
262
1
1
Order By: Relevance
“…Maternal stressors induce changes in expression of the fetal genome, which can permanently alter the offspring’s physiology, development, metabolism, and growth [50], as reported in mice and rats [51,52]. Understanding the effect of poor maternal nutrition in ovine fetal development is not only relevant to agriculture [53], but also to modeling for human pregnancy and fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal stressors induce changes in expression of the fetal genome, which can permanently alter the offspring’s physiology, development, metabolism, and growth [50], as reported in mice and rats [51,52]. Understanding the effect of poor maternal nutrition in ovine fetal development is not only relevant to agriculture [53], but also to modeling for human pregnancy and fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, MD decreased body weight gain and increased total and HDL-cholesterol. In other animal model (agouti mice), Waterland et al [49] described that maternal MD prevented transgenerational increase in adult body weight. Previous investigations had already described the increase of HDL-cholesterol due to betaine [50] and folic acid supplementation [51] in mice and humans, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IR expression in the hippocampus was decreased by MS and reversed by MD. In this sense, studies in rodents have previously focused on the protective effects of dietary supplementation with methyl donors on obesity [49] and hepatic fat accumulation [29,55], suggesting an improvement of diet-induced insulin resistance by activating IR and the downstream signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein-induced epigenetic alterations seems to share important similarities with those found in intrauterine growth retardation neonates (Einstein et al, 2010), but the magnitude is markedly lower than the differences found between tissues or in cancer. As previously described, perinatal undernutrition (Jousse et al, 2011) or overnutrition (Plagemann et al, 2009), the intake of particular nutrients like methyl donors (Waterland et al, 2008) or PUFA (Kiec-Wilk et al, 2011), or the exposure to endocrine disruptors like bisphenol A (Rubin et al, 2011) are crucial in the in utero modulation of the epigenetic marks (DNA methylation or histone modifications), and more efforts must be made to unravel the epigenetic mechanisms involved in the pathogenesis of obesity and metabolic syndrome, including the doses of each compound, the interactions with the genotype and the period or length of the exposure. One interesting example of possible application of this research is the demonstration that leptin administration during the suckling period has protective effects against later obesity probably by inducing changes in promoter methylation of the hypothalamic POMC gene (Palou et al, 2011).…”
Section: Perinatal Events (Gestation and Lactation)mentioning
confidence: 94%
“…A seminal article by Waterland et al (2008) subsequently reported that methyl donor supplementation induces DNA hypermethylation during development and prevents transgenerational amplification of obesity in agouti viable yellow (Avy) mice. After that, many studies have analyzed the epigenetic effects of a diet deficient in methyl donors or with methyl donor supplementation during pregnancy in different metabolic diseases, including altered behavior in offspring (i.e, anxiety) through permanent changes in hippocampal DNA methylation (Konycheva et al, 2011).…”
Section: Methyl Donorsmentioning
confidence: 99%